2022
DOI: 10.1007/s12640-022-00555-x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Potential of Intranasally Delivered Sulforaphane-Loaded Iron Oxide Nanoparticles Against Cisplatin-Induced Neurotoxicity

Abstract: Cisplatin (CIS) is a platinum-based chemotherapeutic drug that is widely used to treat cancer. However, its therapeutic efficiency is limited due to its potential to provoke neurotoxicity. Sulforaphane (SF) is a natural phytochemical that demonstrated several protective activities. Iron oxide nanoparticles (Fe3O4-NPs) could be used as drug carriers. This study aimed to explore the nanotoxic influence of SF-loaded within Fe3O4-NPs (N.SF), and to compare the neuroprotective potential of both N.SF and SF against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 88 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…The intranasal administration of N.SF to the CIStreated rats were found to have neuroprotective functions on the biochemical, histopathological (striatum and cerebral cortex), and behavioral aspects. 40 Other studies have shown the neuroprotective efficacy of Fe 3 O 4 -NPs in fruit y models by executing catalase-like functions. Its neuroprotective roles have been established in PD and AD models in Drosophila.…”
Section: Benecial Effectsmentioning
confidence: 98%
“…The intranasal administration of N.SF to the CIStreated rats were found to have neuroprotective functions on the biochemical, histopathological (striatum and cerebral cortex), and behavioral aspects. 40 Other studies have shown the neuroprotective efficacy of Fe 3 O 4 -NPs in fruit y models by executing catalase-like functions. Its neuroprotective roles have been established in PD and AD models in Drosophila.…”
Section: Benecial Effectsmentioning
confidence: 98%
“…Besides, another clinical trial conducted in China on the treatment of SFN in AD patients is still ongoing (NCT04213391). In terms of the neuroprotective effects of SFN on chemobrain, recent research has shown that SFN-loaded within iron oxide nanoparticles (SFN-Fe 3 O 4 ) via intranasal administration significantly alleviated cisplatin induced neurotoxicology ( Ibrahim Fouad et al, 2022 ). Furthermore, treatment with SFN-Fe 3 O 4 significantly restored GSH and NO contents as well as inhibited the levels of lipid peroxidation (LPO) in rat brain tissues ( Ibrahim Fouad et al, 2022 ).…”
Section: Natural Products For the Treatment Of Crcimentioning
confidence: 99%
“…Chemotherapeutics are the most common and powerful drugs used in elimination of rapidly proliferating tumor cells even in sites far from their primary origin (Schirrmacher, 2019;Sarbaz et al, 2022). The use of chemotherapeutics is clinically limited due to their severe side and toxic effects in recipient body during treatment of malignant tumors (Liu et al, 2016;Brown et al, 2019;Aliwaini et al, 2020;Zavattaro et al, 2021;Fouad et al, 2022).…”
Section: Introductionmentioning
confidence: 99%